Faktor-Faktor Penentu Kualitas Audit Serta Pengaruh Kualitas Audit Terhadap Kepuasan Auditee Pada Pemerintah Daerah - Sarah Raharjo; Luh Putu Mahyuni (Jurnal Manajemen dan Bisnis, 2019)
ABSTRACTThe purpose of the study is to investigate the influence of compliance, independence, professional care, commitment, and skeptical attitude towards audit quality and to empirically test the influence of audit quality on auditee satisfaction.The object of the study was local government of Bali province. As many as 150 questionnaires were distributed, 115 were returned and filled. Data analyzed using Partial Least Square-Structural Equation Modelling (PLS-SEM).The study finds that only proffesional care and skeptical attitude significantly influence audit quality. This study also provides empirical evidence of the influence of   audit quality on auditee satisfaction.